Анализа укорељености нивоа ФАБП3, МЦП-4 и ЦХЦЛ9 и оштећења миокарда код пацијената са тешком пнеумонијом: Нивои ФАБП3, МЦП-4 и ЦХЦЛ9 код оштећења миокарда тешке упале плућа - Du, Longxia; Wang, Jianping; Wu, Zongxian; Lai, Xianxin; Qian, Xuanchen (Journal of Medical Biochemistry, 2025)
[Objective] To explore the correlations between the levels of serum monocyte chemoattractant protein-4 (MCP-4), heart-type fatty acid binding protein (FABP3), and chemokine ligand 9 (CXCL9) and myocardial damage in severe Mycoplasma pneumoniae (SMPP) patients. [Methods] A total of 158 patients with severe Mycoplasma pneumoniae complicated with myocardial damage were included in the SMPP group. They were divided into a myocardial damage group (n=42) and a nonmyocardial damage group (n=116) according to whether myocardial damage occurred. The control group consisted of an additional 102 healthy people who were examined throughout the same time period. The levels of serum MCP-4, FABP3 and CXCL9 in the two groups were compared. The general clinical data of the patients were recorded. Multivariate logistic analysis was conducted to analyze the risk factors for myocardial damage in patients with severe mycoplasma complicated with pneumonia. [Results] The levels of serum MCP-4, FABP3 and CXCL9 in the SMPP group were significantly greater (all P<0.05). Compared with those in the nonmyocardial damage group, Serum MCP-4, FABP3, and CXCL9 levels were considerably higher (all P<0.05) in the group with myocardial injury. Age, sex, diabetes, smoking history, hypoxemia, jaundice, and chronic obstructive pulmonary disease (COPD) did not differ statistically significantly between the two groups (all P>0.05). Compared with those in the nonmyocardial damage group, the proportions of patients with hypertension, coronary heart disease and anemia, as well as the levels of serum MCP-4, FABP3 and CXCL9, in the myocardial damage group were significantly greater (all P<0.05). Combined hypertension, coronary heart disease, anemia, and high levels of serum MCP-4, FABP3, and CXCL9 are risk factors for myocardial damage in patients with severe mycoplasma infection. The levels of serum MCP-4, FABP3 and CXCL9 in patients were positively correlated with the incidence of myocardial damage in patients with severe mycoplasma infection (all P<0.05). [Conclusion] The levels of serum MCP-4, FABP3 and CXCL9 are positively correlated with myocardial damage in patients with severe Mycoplasma pneumoniae. Moreover, combined hypertension, coronary heart disease, anemia and high levels of serum MCP-4, FABP3 and CXCL9 are risk factors for myocardial damage in patients with severe mycoplasma infection. These three factors can be used as biological indicators of myocardial damage in patients with severe mycoplasma infection in clinical practice and are highly important for the assessment of patients’ conditions and the formulation of treatment plans.